Differentiated Islamic Religious Education Learning Based on Hyperdoc Technology for Junior High School Students - Purwaningrum, Septiana (Proceeding International Conference on Education, 2023)
Curriculum changes from the Kurikulum 2013 to the Kurikulum Merdeka require teachers to be creative and innovative in carrying out differentiated learning. Technology is needed to make it easier for teachers to implement it. PAI teachers at SMPN 2 Kepung Kediri have innovated by utilizing Hyperdoc in the differentiated PAI learning. This study aims to describe: 1) different forms of PAI learning in classes IX-G and IX-I on tolerance; 2) implementing PAI learning based on Hyperdoc; and 3) The effectiveness of using Hyperdoc in PAI learning. The research approach used is a qualitative type of case study. Data collection techniques using interviews and documentation. The validity of the collected data was checked by means of technical triangulation. The results can be concluded: 1) Forms of PAI learning are carried out through content, process and product differentiation; 2) The implementation of differentiated PAI learning based on Hyperdoc technology is carried out through the following steps: distributing forms containing questions related to students' interest in art or other; compiling a differentiated Hyperdoc whose material is according to students' interests; PAI learning is carried out by teachers using Hyperdoc in various ways, in groups, and individually; create digital comic projects as a form of reflection on understanding the material that has been taught; and finally presenting the work; 3) The effectiveness of PAI learning by utilizing Hyperdoc can be seen through the positive responses of students and the learning outcomes of students who have achieved the Learning Objectives Achievement Criteria.